2019
DOI: 10.1039/c9ra02027f
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced electron transfer in novel CdSe–Cu2Se type II core–shell quantum dots

Abstract: Herein we report the synthesis, characterisation and electron transfer studies of CdSe–Cu2Se QDs, a novel type II core–shell system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…[31][32][33] Ptype doping of CdSe with Cu 2 Se can tune the bandgap of CdSe for varying its optical response and this can improve the photocurrent conversion efficiency by providing extra holes. Simi et al 34 reported the synthesis of type II core-shell quantum dots by a high temperature organometallic method. They inferred that the charge separation in the CdSe-Cu 2 Se core-shell system makes it a good choice for designing light harvesting devices.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] Ptype doping of CdSe with Cu 2 Se can tune the bandgap of CdSe for varying its optical response and this can improve the photocurrent conversion efficiency by providing extra holes. Simi et al 34 reported the synthesis of type II core-shell quantum dots by a high temperature organometallic method. They inferred that the charge separation in the CdSe-Cu 2 Se core-shell system makes it a good choice for designing light harvesting devices.…”
Section: Introductionmentioning
confidence: 99%